2016
DOI: 10.5812/ircmj.42562
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium on Ischemia-Reperfusion Injury in the Coronary Artery Bypass Graft Surgery: A Clinical Trial Study

Abstract: Background: In patients with coronary artery stenosis, coronary artery bypass graft surgery (CABG) is the most effective strategy to limit infarct size and improving outcomes. However, the rapid restoring of blood flow to the tissue can paradoxically induce cardiac damage. This phenomenon termed as myocardial ischemic/reperfusion (I/R) injury which is exacerbated under cardiopulmonary bypass (CPB) and is the cause of poor clinical outcomes. Therefore, it is essential to search for novel strategies with further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
1
6
1
Order By: Relevance
“…Nevertheless, these differences did not show a statistically significant threshold. According to our results, selenium administration via cardioplegia solution did not effectively reduce CK-MB level in the patients undergoing CABG, which agreed with the findings of Sedighinejad et al (20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, these differences did not show a statistically significant threshold. According to our results, selenium administration via cardioplegia solution did not effectively reduce CK-MB level in the patients undergoing CABG, which agreed with the findings of Sedighinejad et al (20).…”
Section: Discussionsupporting
confidence: 92%
“…T2), the differences were not statistically significant. However, this observation was opposed to the finding of Sedighinejad et al (20) at 6 hours postoperation (i.e. T2).…”
Section: Discussioncontrasting
confidence: 78%
“…The protective effects of selenium during oxidative stress have been shown (8)(9)(10)(11)(12). In some experimental studies, selenium supplementation could decrease postoperative complications after cardiac surgery and affected the stress oxidative process (9,13).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the included studies reported an overall low risk of bias, enhancing the authenticity of this meta analysis. Out of the 7 included studies, 3 studies reported detection bias which was the only main factor that hindered the quality of included studies ( 18 , 21 , 22 ). Additionally, the trial conducted by Amini et al reported performance bias ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four of seven RCTs ( 16 , 17 , 21 , 22 ) compared data on the post-operative CK-MB levels between selenium-supplemented and control group patients. A marginal difference was found in the postoperative CK-MB levels between the two groups (WMD = 0.73; 95% CI = −6.80–8.26; P = 0.85; I 2 = 95%).…”
Section: Resultsmentioning
confidence: 99%